2005
DOI: 10.1007/bf03324630
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s views of prioritization in health care

Abstract: Older people's views of priorities seem to differ from previous population-based studies, in that age per se as a criterion for selection between patients was not favored; health and wellbeing were more important. Differences were, however, found within the group of older people, as regards both age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This is also in line with earlier quantitative research concerning older people's views about prioritisation, showing that a majority, 81 %, did not want prioritisation in health care to be based on age, neither in terms of youth nor old age. Instead, factors such as quality of life, pain and health had higher impact on how they wanted people to be prioritised for treatment (5). This is also in line with Dicker and Armstrong (27) who showed in interview study from UK (n=16, aged 20-73) that the single most important attribution that interviewees identified as a determinant of their opinions concerning prioritisation was visible unmet need.…”
Section: Discussion Of the Findingssupporting
confidence: 70%
See 2 more Smart Citations
“…This is also in line with earlier quantitative research concerning older people's views about prioritisation, showing that a majority, 81 %, did not want prioritisation in health care to be based on age, neither in terms of youth nor old age. Instead, factors such as quality of life, pain and health had higher impact on how they wanted people to be prioritised for treatment (5). This is also in line with Dicker and Armstrong (27) who showed in interview study from UK (n=16, aged 20-73) that the single most important attribution that interviewees identified as a determinant of their opinions concerning prioritisation was visible unmet need.…”
Section: Discussion Of the Findingssupporting
confidence: 70%
“…The quantitative results of that study have been presented previously (5,6). The first 500 interviews were tape-recorded and 300 were selected for this study.…”
Section: Sample and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Stories about murders and suicides committed by people who have tried unsuccessfully to get help from psychiatric clinics have received a great deal of attention in the media over the last few years. This might explain why politicians and physicians, as well as (in an earlier study [19]) older people (60-100 years), ranked psychiatric care highest on the list of disciplines needing more resources. The view of the physicians that elder care needs more resources might be explained by the large group of older patients who remain in hospitals, even though treatment has been completed, because of lack of beds in special accommodation.…”
Section: Discussionmentioning
confidence: 94%
“…This research team also found that physicians were less willing than the other groups to refer older patients for elective surgery (Ryynanen et al, 1997). Even so, it has been shown in several studies that the general public has confidence in physicians as decision makers in priority settings but not in politicians (Werntoft et al, 2005a, Werntoft et al, 2007. The views of physicians and politicians on age-related prioritisation in healthcare are, however, not well known.…”
Section: Introductionmentioning
confidence: 91%